An Organizational Approach to the Assessment of the Reengineering of the Enterprise’s Business Processes - Rybalko-Rak Lesіa A.; Opryshko Volodymyr I.; Bilan Leonid P.; Derzhii Ruslan V. (Bìznes Inform, 2023)
In the context of constant aggravation of competition, when the speed of response of all subsystems of the enterprise along with the efficiency of activities are of particular importance, one of the effective instruments aimed at improving the functioning of the enterprise is the reengineering of business processes, since it radically changes the existing process model of business to an innovative model that is more adaptive to the existing realities of an economic entity. Effective use of technologies and instruments for reengineering of business processes allows the enterprise to become more flexible and adaptive to changes in the external environment, and as a result, more competitive in the business environment. Therefore, the study of the scientific problem of the application of the conception of reengineering and its implementation by enterprises in today’s conditions is an urgent task of both scientists and practitioners. The aim of the article is to develop an algorithm for evaluating the process of reengineering of the enterprise’s business processes. The article proves the relevance of the conception of reengineering of the business processes of enterprise by analyzing the evolution, formation, and the current development of this sphere of knowledge; the importance of information technologies in the management of the system of processes and modeling of the business processes of enterprise is determined; the stages of the procedure for reengineering of the business processes of enterprise are substantiated and the role and status of personnel in these changes are determined; an integrated organizational approach to assessing the process of reengineering of the the enterprise’s business processes has been substantiated. The purpose of the research was achieved with the help of a system of methods, in particular analysis and synthesis, induction and deduction – to determine the essence and features of the object and subject of research, scientific abstraction, logical analysis, comparison – to establish the causes, factors, and consequences of influence on the object and subject of research; integrated and system approach – to assess the process of reengineering of the business processes of the enterprise. Further scientific research on the subject of research will be based on the rapid development of modern technologies with the progressive informatization of society, which will lead to new conceptions and approaches both to the organization of reengineering and to the evaluation of its results.